The Influence of Employee Wellbeing and Employee Resilience on Innovation Work Behavior Mediated By Work Climate in the Insurance Industry in DKI Jakarta - Zeanette T. LISBET; Willy ARAFAH; Deasy ASEANTY (Indonesia Strategic Sustainability, 2023)
This study analyze the effect of employee wellbeing and employee resilience on innovative work behavior mediated by the work climate in the insurance industry in DKI Jakarta. This research method uses a quantitative approach, tested by Structural. Equation Modeling with the help of the Amos program. The sampling method uses purposive sampling. The data was collected using a questionnaire which was distributed randomly to all departments of 3 (three) life insurance companies and 3 (three) general insurance companies via a google form. The findings in this study indicate that there is no positive effect of employee wellbeing on innovation work behavior, there is a positive influence of employee resilience on innovation work behavior, and there is a positive effect of employee wellbeing on hybrid work climate., There is no positive effect of employee resilience on a hybrid work climate., there is a positive effect of hybrid work climate on innovation work behavior, there is an effect of employee wellbeing on innovation work behavior mediated by hybrid work climate, there is no effect of employee resilience on innovation work behavior mediated by hybrid work climate, there is no effect of hybrid work climate on innovation work behavior moderated by gender. The findings of this study have management implications that management can improve human resource development to identify and maintain resilience qualities in employees and influence them with specially designed interventions. In addition, a company climate that supports creativity and innovation also contributes to the emergence of innovative behavior in the workplace.